Behind the white coat: Unraveling the patterns of workplace violence in an Italian healthcare setting – An epidemiological exploration - Claudio Terranova; Clara Cestonaro; Federico Ferrari; Ludovico Fava; Alessandro Cinquetti; Anna Aprile (PLoS ONE, 2025)
Aim In the present study, we aimed to provide an epidemiological and descriptive overview of violence against healthcare workers in an Italian university hospital, presenting and characterizing the risk factors in the department where such events occur and to propose ways to prevent aggressive behaviors. Methods We retrospectively analyzed violence against healthcare workers by patients and attendants at an Italian university hospital from 2020 to 2022. Aggressions were documented in anonymous incident reports collected by the hospital’s Clinical Risk Unit. The frequencies and percentages were calculated via a descriptive analysis. Chi-square tests were used to compare the wards with the most aggressions to other wards. Results Of the 219 included cases, the aggressors were primarily male patients and the victims female nurses. Most of the aggressions occurred in the psychiatry and emergency department. Among the aggressors, 41.1%, had a psychiatric diagnosis or neurocognitive impairment. Over half the cases involved physical aggression. Compared to other wards, psychiatric wards showed an even distribution of aggressor gender, a higher proportion of male victims, fewer verbal aggressions, and less impact from environmental factors. Notably, female aggressor status (p < 0.001, OR = 8.687) and involvement in physical assaults (p < 0.001, OR = 15.236) were identified as independent risk factors associated with aggression in psychiatric settings. Conclusion Our findings align with the literature in that most of the incidents occurred in the psychiatry and emergency medicine departments and involved nurses. However, physical rather than verbal aggression predominated. Notable distribution, risk factor, and qualitative differences were observed between the psychiatric and non-psychiatric services, which warrants further investigation. Our results could be useful in implementing better prevention strategies based on the type of ward.